REPRESENTATION OF HARD-BOILED DETECTIVE FORMULA IN THE BATMAN (2022) BY MATT REEVES - Jidan Mustopa; Yoga Sudarisman (Saksama, 2022)
This research focuses on finding the action patter of hard-boiled detective formula and its effect to the main character in The Batman (2022) movie by Matt Reeves using John G. Cawelti theory of hard-boiled detective formula, the action pattern of hard-boiled detective formula was detective as a hero, suspense and threat, a modern city as a background, the role of women and changing meaning Furthermore, this research used the qualitative descriptive method. This method aims to examine text and image data, have unique steps in data analysis and draw on diverse designs. This method was used to analyze the data from the visual and narrative standpoint because those elements can be represented through both of them. The result of this research is the representation of Hard-boiled detective formula in The Batman movie. The action pattern were presented in the form of narrative structure especially on plot, characters, and dialogue. Those elements can have effects to the main character development, for example a modern city as a background depicted the corruption, and death, a moral wasteland in which crime pre dominants.